If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y(Y) + 10Y + -264 = 0 Multiply Y * Y Y2 + 10Y + -264 = 0 Reorder the terms: -264 + 10Y + Y2 = 0 Solving -264 + 10Y + Y2 = 0 Solving for variable 'Y'. Factor a trinomial. (-22 + -1Y)(12 + -1Y) = 0Subproblem 1
Set the factor '(-22 + -1Y)' equal to zero and attempt to solve: Simplifying -22 + -1Y = 0 Solving -22 + -1Y = 0 Move all terms containing Y to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + -1Y = 0 + 22 Combine like terms: -22 + 22 = 0 0 + -1Y = 0 + 22 -1Y = 0 + 22 Combine like terms: 0 + 22 = 22 -1Y = 22 Divide each side by '-1'. Y = -22 Simplifying Y = -22Subproblem 2
Set the factor '(12 + -1Y)' equal to zero and attempt to solve: Simplifying 12 + -1Y = 0 Solving 12 + -1Y = 0 Move all terms containing Y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1Y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1Y = 0 + -12 -1Y = 0 + -12 Combine like terms: 0 + -12 = -12 -1Y = -12 Divide each side by '-1'. Y = 12 Simplifying Y = 12Solution
Y = {-22, 12}
| -6x+5y=45 | | 0.5(4x-5)+0.4=10 | | -243=-90(9x) | | 4a+10=16 | | -6-(-1/2)n=8 | | -6-(-1/2)=8 | | 180/x=x/(180-x) | | 2.5x-0.75(2x+5)=0.37 | | =3(-2C-5D)+2D-5(D-3C) | | 1/2b-3=3/4 | | y-5=1/5(x-1) | | x^2-6x-y^2-y+10=0 | | 72=a(-18+16)(-18+2) | | 11-2x-7+42-3x=2 | | 5x^2-4=19x | | 56.25=x(1+.25) | | 99999999999999999+9999999999999= | | X=45+-4x | | log(5x+7)=0 | | m=23 | | 3*13y= | | x-(.10x)=50000 | | 8x-3=8x+5 | | (6ab^4/3x^-3y^-4)^-2=0 | | 22+8=1763014 | | x=50000+.10x | | (2x-5)(2x^2+10x+25)=0 | | X=6(3a+4c) | | x-.10x=50000 | | -5x(3)+30x(2)-15x=90 | | 2x-8x+1=9-16x | | ax+bx-cx-ay+dy-ey= |